A flexible millimeter-wave radio-over-fiber system for various transmission bit rate. (1st November 2017) - Yang, Tao; Gao, Mingyi; Qian, Jiaqin; Zhang, Junfeng; Chen, Wei
Highlights: Good frequency multiplication can be obtained without complex system structure. Q-band and V-band MMWs can be obtained simultaneously. Our system is flexible and can accommodate different transmission requirements. Transmission rate and distances can reach to 40-Gb/s and 50 km, respectively. Abstract: In this paper, we propose a flexible scheme to generate millimeter-waves (MMWs) for millimeter-wave radio-over-fiber (MMW-RoF) system. The proposed scheme has two configurations to adapt to various transmission bit rate by slightly rearranging the allocation of the system. The main structure of the system is cascaded LiNbO3 Mach-Zehnder modulators (LiNbO3 -MZMs). The first configuration is cost effective method, where we utilize a wavelength division multiplexing de-multiplexer (WDM Demux) and an optical splitter (OS) to generate two unmodulated optical signals and a modulated optical signal. Each unmodulated optical signal and the modulated signal will form an optical single sideband (OSSB) modulation and therefore we simultaneously achieve a Q-band (45 GHz) and a V-band (60 GHz) MMWs in the receiver. The bit-error-ratio (BER) curves show that the power penalties of 45 GHz and 60 GHz are 0.6 dB and 1.1 dB at a BER of 1 × 10 −9 with 2.5 Gb/s transmission data rate and 50 km fiber transmission distances. The second configuration can accommodate high bit rate, where few optical devices is rearranged to only generate a 60 GHz MMW with 40 Gb/s 4 quadrature amplitude modulation orthogonal frequency division multiplexing (4-QAM OFDM) signals. The power penalty is 1.1 dB at a BER of 1 × 10 −9 with 50 km fiber transmission distances. Therefore, the proposed scheme can flexibly generate either two Q&V-band MMWs (45 GHz and 60 GHz) for the applications of the low data-rate transmission systems or one V-band MMW (60 GHz) for the applications of the high data-rate transmission systems.